2021
DOI: 10.1002/clc.23526
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after readmission at the index or nonindex hospital following acute myocardial infarction complicated by cardiogenic shock

Abstract: Little is known about the prevalence and outcomes of readmission to nonindex hospitals after an admission for acute myocardial infarction complicated by cardiogenic shock (AMI‐CS). We aimed to determine the rate of nonindex readmissions following AMI‐CS and to evaluate its association with clinical factors, hospitalization cost, length of stay (LOS), and in‐hospital mortality rates. Hypothesis Nonindex readmission may lead to worse in‐hospital outcomes. Methods We reviewed the data of inpatients with AMI‐CS be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Several studies have evaluated the positive clinical effects of continuity of care, or interventions facilitating continuity of care, for patients with cardiac conditions. These clinical effects include reduced mortality and complications [29][30][31][32] , reduced healthcare utilization and fewer hospitalizations [32][33][34][35][36][37] , reduced 30-day readmission rate 29,32,[38][39][40][41][42][43][44][45][46] , reduced visits to the emergency department 32,34,37,45 , and shorter lengths of hospital stay (LOS) 29,31,47 . In addition, insufficient continuity is associated with inappropriate prescription medications (i.e., the use of drugs that should be avoided due to the high risk of adverse events) in patients with comorbidity 37 and serious adverse drug reactions in patients with atrial fibrillation using oral anticoagulation 48,49 .…”
Section: Continuity Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have evaluated the positive clinical effects of continuity of care, or interventions facilitating continuity of care, for patients with cardiac conditions. These clinical effects include reduced mortality and complications [29][30][31][32] , reduced healthcare utilization and fewer hospitalizations [32][33][34][35][36][37] , reduced 30-day readmission rate 29,32,[38][39][40][41][42][43][44][45][46] , reduced visits to the emergency department 32,34,37,45 , and shorter lengths of hospital stay (LOS) 29,31,47 . In addition, insufficient continuity is associated with inappropriate prescription medications (i.e., the use of drugs that should be avoided due to the high risk of adverse events) in patients with comorbidity 37 and serious adverse drug reactions in patients with atrial fibrillation using oral anticoagulation 48,49 .…”
Section: Continuity Of Carementioning
confidence: 99%
“…It is difficult to compare the results in relation to cardiac diagnoses with previous studies. Some studies on continuity of care do not report specific diagnoses 182 , only include one diagnosis 17,[29][30][31][42][43][44]180 , only include one cardiac condition 33,34,37,40,41,89 or do not present their findings in a way that makes a comparison between diagnoses possible 38 . However, Valaker et al 180 found that patients with an acute clinical pathway, such as those hospitalized due to STEMI, perceived significantly higher levels of informational and management continuity than patients with a non-acute clinical pathway, such as stable angina pectoris.…”
Section: Perceived Continuity After Hospitalizationmentioning
confidence: 99%